Does Economic Policy Uncertainty Affect Exchange Rate in China and Japan? Evidence from Threshold Cointegration with Asymmetric Adjustment - El Abed, Riadh; Mighri, Zouheir; Hamouda, Abderrazek Ben (International Journal of Economics and Financial Issues, 2022)
In this article, we estimate the links between nominal exchange rates (JPY/USD and CNY/USD) and economic policy uncertainty (EPU) in China and Japan by employing monthly data during the period span from January 1997 to September 2020. The threshold cointegration approach focus in TAR, M-TAR, C-TAR and C-MTAR is used. Results indicate the evidence of asymmetric effect in the adjustment process to equilibrium and the M-TAR is the best model to detect threshold effect for the (CNY/USD-CNYEPU) pair and the C-TAR is the best model to detect threshold effect for the (JPY/USD-JPYEPU) pair.